RELASI KEKUASAAN DALAM WACANA PENERAPAN QANUN JINAYAT DI ACEH - Maulina, putri (Universitas Teuku Umar, 2017)
Implementation of Islamic Sharia in Aceh not only involve to the Muslim society as the majority,but also non-Muslim minority society. One of the laws that applied in Aceh is Qanun Jinayat.Implementation of Qanun Jinayat as part of the Islamic law involving multiple parties in arelationship of power. In this case, the Aceh government and the mass media are the 'power'which determines the dominant discourse in the society. This qualitative study will describe howthus power manifested in such discourse of the media. Eventually, the result of study showed thatthe issue of enforcement of Qanun Jinayat takes the interests of the dominant ruler through theuses of language in the mediaKeywords: Power Relations, Govermentality, Sharia Law, Qanun Jinayat